Structural characterization of the major ampullate silk spidroin-2 protein produced by the spider Nephila clavipes - Aparecido dos Santos-Pinto, Jose Roberto [UNESP]; Arcuri, Helen Andrade [UNESP]; Lubec, Gert; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2016)
Major ampullate spidroin-2 (MaSp2) is one of the most important spider silk protein, but up to now no information is available regarding the post-translational modifications (PTMs) of this protein. A gel-based mass spectrometry strategy using collision-induced dissociation (CID) and electron-transfer dissociation (ETD) fragmentation methods was used to sequence Nephila clavipes MaSp2 (including the N- and C-terminal non repetitive domains, and the great part of the central core), and to assign a series of post-translational modifications (PTMs) on to the MaSp2 sequence. Two forms of this protein were identified, with different levels of phosphorylation along their sequences. These findings provide a basis for understanding mechanoelastic properties and can support the future design of recombinant spider silk proteins for biotechnological applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Silk proteins; Nephila clavipes; Mass spectrometry; Post-translational modification; Phosphorylation